Box Girder Bridge Design - Kavanagh, Thomas C. (Engineering Journal, 1967)
This paper discusses the coordinated design research program conducted under the sponsorship of the United States Steel Corporation, on the subject of steel box girder bridges. The assigned objective of this investigation was the development of design theory, methods and specifications for steel box girder bridges of short to medium span lengths, having composite decks. The work has included both theoretical, computer, and model test studies, and has progressed to the point where a draft of a specification has been prepared by the investigators and a number of interested state and federal highway engineers, for presentation to the AASHO Bridge Committee. The use of torsion boxes as flexural girders in bridges is but another extension of the advantageous application of closed structural sections as columns, arch ribs, truss members, or stiffeners for deck plates, where it is desired to achieve improved structural strength, economy, appearance, and resistance to corrosion. Even a cursory survey of current bridge literature will indicate a growing awareness of the potential importance of box girders.